PEMBERDAYAAN ASSET TANAH WAKAF DAN NON WAKAF SEBAGAI SARANA PENDIDIKAN DI PIMPINAN WILAYAH MUHAMMADITYAH JAMBI - Fetrimen, Fetrimen (Universitas Muhammadiyah Prof DR HAMKA, 2016)
Many assets land owned Muhammadiyah untapped by Persyarikatan Muhammadiyah started at the level of the branches to the central level, when the assets of the land owned by the waqf faith professed by wakif to use educational facilities or social amenities more, then the assets of the land was put to good use, so that assets such land lots used by the community because of the land ownership are not yet using the name Persyarikatan but many are using personal names or on behalf of the chairman Persyarikatan and ownership are obvious, like any asset of land have a certificate of good certificate endowments as well as a certificate of non endowments. It also occurs in the scope of the Regional Chairman of Muhammadiyah Jambi. As this study include land assets and non endowments Muhammadiyah Regional Leadership within the scope of the Regional Chairman of Muhammadiyah Jambi. In addition, the need to be formulated is a status, certification of land endowments, non endowments land titling, land asset status is certified in Muhammadiyah Regional Leadership within the scope of the Regional Chairman of Muhammadiyah Jambi.The method used in this study is a survey method. Survey methods in research designed to obtain information about the status and symptoms during the study was conducted to describe the variable or about something in a condition. This research method, gives an overview of concrete empowerment existing land assets through inventory Jambi region. Therefore, this study method is designed to reveal the factual data based on information found at the time to survey the Muhammadiyah Regional Leadership in Jambi.